Clinical Effect of Acupuncture Combined with Traditional Chinese Medicine Application on the Treatment of Functional Dyspepsia in Children and the Influence on Serum 5-HT and NO Levels. (31st March 2022) - Li, Junxia; Nie, Qiuhua; Chen, Hongyu
Abstract : Objective . To explore the clinical effect of acupuncture combined with traditional Chinese medicine (TCM) application on the treatment of functional dyspepsia (FD) in children and the influence on serum 5-HT and NO levels. Methods . 94 FD children admitted to the pediatric department of our hospital from March 2019 to March 2020 were selected as the research object and divided into the study group ( n  = 45) and reference group ( n  = 49) by the number table method. The routine Western medicine therapy was given to the reference group and the combination therapy of acupuncture and TCM application was given to the study group to analyze the effect of different therapies on FD children by detecting their serum 5-hydroxytryptamine (5-HT) and nitric oxide (NO) levels and electrogastrogram (EGG) before and after treatment. Results . The sex ratio, mean age, mean duration of disease, mean weight, mean BMI value, and residence of children in the two groups were not significantly different (P > 0.05 ); after treatment, the study group obtained significantly lower symptom scores and shorter disappearance time of clinical symptoms when comparing with the reference group (P < 0.001 ); the total clinical effective rate of the study group was significantly higher than that of the reference group (P < 0.05 ); the treated serum 5-HT and NO levels of children in both groups were significantly lower than those before treatment (P < 0.05 ), and in the between-group comparison, those of the study group were significantly lower (P < 0.05 ); and the treated AP, FP, and normal slow wave ratio of gastric antrum and body were significantly higher in the study group than in the reference group (P < 0.05 ). Conclusion . The combination therapy of acupuncture and TCM application is a reliable method for improving the clinical symptoms in FD children. This strategy greatly reduces the levels of serum factors in child patients and shortens the corresponding treatment time. Further research will be conducive to establishing a better solution for such patients.